Attitude of health care workers towards acute flaccid paralysis surveillance system in Al-Najaf city - Halah J. Jasim; Najat H. Hassan (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: As the gold standard for poliomyelitis case detection, acute flaccid paralysis (AFP) surveillance is an important method for monitoring progress toward the global eradication goal of poliomyelitis. Aim of study: To evaluate health workers’ attitudes regarding Acute flaccid paralysis (AFP) in primary healthcare centers Najaf city. Methods: cross-sectional descriptive study was carried out in 18 primary healthcare centers located in 2 districts of Najaf city, using the method of simple random sampling technique. The research study includes 210 primary healthcare workers. A questionnaire was used to evaluate the acute flaccid paralysis attitudes of healthcare workers. Data collection from November 1, 2023, to the of February 31, 2024.Result: The results showed that health workers’ assessment of their attitudes about the reporting case of AFP was good (2.35±0.684) and about Laboratory prosses case of AFP was fair (2.31±0.656). there is statistical significance between the attitude of health care workers and Age group/years, Education level, Specialists and experimental years in PHCs where P value (0.012, 0.012, 0.000, 0.002 respectively). Conclusion: Health care workers’ attitudes about surveillance of acute flaccid paralysis were fair.